Attention and Aesthetic Experience. - Fazekas, Peter (Journal of Consciousness Studies)
This paper critically analyses a recent attempt to account for what is special about aesthetic experiences in terms of how one deploys one’s attentional resources, i.e. how so-called aesthetic attention is exercised. While the paper defends this general framework of thinking about aesthetic experiences, it argues that the specific characterization of aesthetic attention that has been proposed is unsatisfactory, since it is incompatible with recent empirical findings on how the allocation of attention works. The major aim of this paper is to explore empirically plausible ways of attending, and to determine what scientifically legitimate kind of attention could account for at least some of the distinctive features of aesthetic experiences. The paper argues that the rapid sequential reallocation of the focus of attention to different properties of a single object plays a crucial role in this context.